Los “estándares” en la educación matemática de los Estados Unidos: contexto, reforma y lecciones (ING) - Ruiz, Angel; Chavarría, Jesennia (Uniciencia, 2003)
We examine the Mathematics Reform promoted by the National Committee of Teachers of Mathematics of the United States, based on principles and stardars. Before that, we describe the global historical scenario and, later, the implications and lessons from this educational experience to the world.